BANTUAN HUKUM OLEH DIVISI HUKUM POLISI REPUBLIK INDONESIA YANG MELAKUKAN TINDAK PIDANA (STUDI PUTUSAN NOMOR : 372/PID.B/2020/PN.JKT.UTR.): Legal Assistance By The Legal Division Of The Republic Of Indonesia Police Who Commit Criminal Offenses (Study Decision Number: 372/Pid.B/2020/PN.Jkt.Utr.) - De Rinus, Maria Filfrida; Setiyono (AMICUS CURIAE, 2024)
- Provision of Legal Assistance provided by the Legal Division of the Police of the Republic of Indonesia to Police officers who have committed Serious Abuse in Decision No: 372/pid.B/2020/PN.Jkt.Utr. The main problem of this thesis is whether the provision of legal assistance by the Legal Division of the Indonesian Police to members of the Police who committed criminal acts of serious abuse in Decision No. 372/Pid.B/2020/PN.Jkt.Utr. and whether the consequences of using the Advocate Attributes provided by the Legal Division of the Indonesian Police are in accordance with existing laws and regulations. The type of research used is normative juridical using secondary data, qualitative data analysis, and drawing conclusions using deductive methods. Based on the analysis, it is known that the provision of legal assistance by the National Police Legal Division to Police Officers in the Crime of Serious Persecution is in accordance with National Police Chief Regulation no. 2 of 2017 which is in conflict with article 13 paragraph (2) of PP No. 3 of 2003 concerning the Implementation of Institutional Technical General Courts for Members of the Indonesian Police and the use of advocate attributes by the police in trials is contrary to Constitutional Court decision No.: 89/PUU-XV/2017 and Article 25 paragraph (1) Law no. 18 of 2003 concerning Advocates.